THE INFLUENCE OF LEARNING DISCIPLINE AND PEER ENVIRONMENT ON LEARNING OUTCOMES OF BUSINESS ECONOMY IN CLASS X AT ONE OF SMK NEGERI IN JAKARTA - Rahmadi, Rico Tri; Zulaihati, Sri; Susanti, Santi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This research aims to determine the effect of learning discipline and peer environment on learning outcomes of business economics subjects in class X at one of SMK Negeri in Jakarta. The population of this research was 252 students. The sampling technique used proportional random sampling to obtain a sample of 147 students. The results of this research are: (1) There is a positive and significant influence between learning disciplines on learning outcomes as indicated by tcount> ttable which is 5.097> 1.97658. (2) There is a positive and significant influence between the peer environment on learning outcomes as indicated by tcount> ttable which is 3.232> 1.97658. (3) There is a positive and significant influence between learning discipline and peer environment on learning outcomes as indicated by the value of Fcount> Ftable which is 33.833> 3.06.